Military Environics -- Water, Waste Water, and Solid Waste - Mahoney, James A. (1970)
The information gained of the United States Armed Forces effort, in the areas of water supply, waste water treatment and solid waste disposal is summarized. The report surveys the state of the art of environmental engineering associated with the military environment. The responsibilities of the military civil engineers and the service laboratories and their locations are discussed. Waste products produced by human activities, namely, sewage, its collection, treatment, and disposal are included. Solid wastes are also discussed. Pages missing in original dacument.